What does my future hold? : 99 ways to plan your life - Hall, Judi. (New York : Penguin Compass, 2001)
"From palmistry and dice to sun signs and Egyptian tablets, a collection of ancient oracles that reveal your true destiny"--Cover.
Includes bibliographical references (p. 192) and index.
Keywords: Divination; Fortune-telling.